On the set of eigenvalues of some PDEs with homogeneous Neumann boundary condition. (April 2015) - Fărcăşeanu, Maria; Mihăilescu, Mihai; Stancu-Dumitru, Denisa
Abstract: We analyze an eigenvalue problem, involving a homogeneous Neumann boundary condition, in a smooth bounded domain. We show that the set of eigenvalues of the problem possesses a continuous family of eigenvalues plus exactly one more eigenvalue which is isolated. Our results complement those obtained in Mihăilescu (2011).